PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 SOLOK SELATAN TAHUN PELAJARAN 2013/2014 - Dian Putra, Hengri; Delsi K, Delsi K; sovia, Anny (Pendidikan Matematika, 2014)
ABSTRACTÂ The Â research is based on the students understanding mathematical concepts are low and the students like to ask to her friends reather than to teachers. So low students learning out comes VIII-grade of SMPN 4 Solok Selatan of year 2013/2014. The purpose of this research is to know whether the students understanding mathematical concepts by applying the snowball throwing cooperative learning model is better than using the conventional learning for the VIII-grade students of SMPN 4 Solok Selatan. This is experimental research with random to subject design. The population in this research is the VIII-grade students of SMPN 4 Solok Selatan. The technique of sample classes were determined randomly. The instrument used in this research is test for the understanding mathematical concepts. Based on the result of data analysis, it is know that both sample classes distribute normally and homogenously. So that the hypothesis is accepted, that means that the students mathematical concept apprehension. Using the snowball throwing cooperative learning model is better than that using the conventional learning for the VIII-grade students of SMPN 4 Solok Selatan.